Bamboo-like carbon nanofiber loaded with nickel-cobalt alloy and preparation method and application of bamboo-like carbon nanofiber

Nickel-cobalt organic frame derivatives were prepared by hydrothermal method and loaded on bamboo-shaped carbon nanofibers, which solved the problem of difficult OER kinetics and poor catalyst stability in the existing electrolytic hydrogen production technology, and achieved efficient and low-cost OER catalytic performance.

CN119710789AActive Publication Date: 2025-03-28SHANGHAI UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411796202.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-28
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

In the existing electrolytic hydrogen production technology, the kinetics of redox reaction (OER) are difficult to carry out, precious metal catalysts are costly, scarce resources and poor stability, and the lack of support materials for non-precious metal catalysts leads to poor stability.

Method used

The nickel-cobalt organic frame derivative was prepared by hydrothermal method, and added together with nickel nitrate to a polyacrylonitrile solution to prepare bamboo-like carbon nanofibers, and successfully loaded the nickel-cobalt alloy to form an efficient catalytic network.

Benefits of technology

The hydrogen analysis performance of electrolytic water is improved, the overpotential during the catalytic process is reduced, the conductivity and structural stability are enhanced, and the catalytic activity and durability of OER are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710789A_ABST
    Figure CN119710789A_ABST
Patent Text Reader

Abstract

The invention discloses a nickel-cobalt alloy loaded bamboo-like carbon nanofiber as well as a preparation method and application thereof. The method comprises the following steps: firstly, synthesizing nickel salt and cobalt salt into a spherical nickel-cobalt metal organic framework (NiCo-MOFs) by using a hydrothermal method, then jointly adding the NiCo-MOFs and nickel nitrate into a polyacrylonitrile solution, uniformly mixing, preparing a fiber membrane of a metal organic matter by using an electrostatic spinning method, and finally preparing the nickel-cobalt alloy loaded bamboo-like carbon nanofiber through calcination and carbonization reaction. Due to the catalytic synergistic effect of the nickel-cobalt alloy, the excellent conductivity, large specific surface area and structural stability of the carbon nanofibers and the unique bamboo-like structure of the carbon nanofibers, an efficient catalytic network is formed in the bamboo-like carbon nanofibers loaded with the nickel-cobalt alloy. The preparation process is easy to control, raw materials are cheap and easy to obtain, and the method is suitable for large-scale production. The bamboo-like carbon nanofiber loaded with the nickel-cobalt alloy, prepared by the method, shows excellent water electrolysis oxygen evolution performance, and shows low overpotential, high catalytic activity and durability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a bamboo-shaped carbon nanofiber loaded with nickel-cobalt alloy and a preparation method and application thereof, belonging to the technical field of electrochemical catalyst preparation. Background Art

[0002] Fossil energy has long supported the rapid development of the global economy, but its negative impact on the environment is becoming increasingly serious. The burning of fossil energy has led to environmental problems such as climate change, air pollution, resource depletion and ecological damage. Therefore, the increase in energy demand and environmental pollution has stimulated the research of clean energy such as hydrogen energy. Hydrogen is one of the most promising alternatives to fossil fuels. As a clean energy, hydrogen has the advantages of zero emissions, energy storage and convenient transportation. It can effectively reduce carbon emissions and air pollution and support the transformation of energy structure. It is widely used in transportation, industry and other fields, providing an important solution for the global realization of sustainable development goals and green and low-carbon transformation.

[0003] Methods for producing hydrogen by decomposing water include photolysis, electrolysis, pyrolysis and biomass catalytic hydrolysis. Photolysis uses sunlight to irradiate catalysts to decompose water, but the efficiency is low and is limited by material properties. Pyrolysis decomposes water at high temperatures, which consumes a lot of energy and relies on fossil fuels, which may lead to carbon emissions. Biomass catalytic hydrolysis decomposes water through biological catalysts, but the efficiency and stability of the catalysts are low, making it difficult to apply on a large scale. In contrast, electrolysis of water to produce hydrogen has significant advantages. It decomposes water molecules through electric current, has high efficiency and can be combined with renewable energy to support the production of green hydrogen. When there is a surplus of renewable electricity, electrolysis of water can be used as a means of energy storage to provide a flexible supply of hydrogen, and can achieve zero carbon emissions when driven by renewable energy.

[0004] Although water electrolysis has advantages that other methods cannot match, water electrolysis technology also faces a series of challenges. Water electrolysis is divided into two reaction steps: hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). The OER reaction is an oxidation reaction with a four-electron transfer process, so the reaction kinetics of the OER reaction is more difficult to carry out than the HER reaction. Therefore, the OER reaction has become the focus of scientific researchers in recent years.

[0005] Among various materials, noble metal catalysts have achieved excellent electrocatalytic performance in OER, such as platinum, iridium and ruthenium. Although these catalysts have good catalytic performance, there are several obvious problems: 1) high cost, which limits large-scale application; 2) scarce resources, especially iridium and ruthenium, which are difficult to supply continuously; 3) poor stability, which may cause catalyst dissolution or deactivation in long-term use, reducing catalytic efficiency; 4) low selectivity, which may lead to side reactions and increase energy consumption. Therefore, the development of new, low-cost, and highly stable catalysts (such as transition metal oxides and carbon-based materials) has become the key to breaking through this bottleneck.

[0006] Non-precious metal catalysts such as iron, cobalt, and nickel-based catalysts are low-cost, abundant in resources, and have good catalytic activity, but due to the lack of supporting materials, they are easy to agglomerate, fall off, and have poor stability. Among them, metal supporting materials, such as nickel foam, have the disadvantages of low surface activity, poor corrosion resistance in acidic and alkaline environments, weak bonding between catalysts and supporting materials, and poor structural stability. Carbon-based supporting materials such as carbon nanotubes, carbon cloth, and graphene have good conductivity, strong chemical stability, and can enhance stability. However, these materials have a small surface area and are prone to deformation under high current density. They have insufficient mechanical strength and may cause catalyst failure during long-term operation. These deficiencies limit the long-term application effect of carbon-based materials in water electrolysis, so further optimizing the design of materials has become the current research focus. Summary of the invention

[0007] The object of the present invention is to provide bamboo-like carbon nanofibers loaded with nickel-cobalt alloys and a preparation method and application thereof in view of the deficiencies in the prior art. The method first uses a hydrothermal method to prepare a nickel-cobalt organic framework derivative, and then adds it and nickel nitrate into a polyacrylonitrile solution for full stirring, and prepares carbon nanofibers. The method preparation process of the present invention is easy to control, and the raw materials are cheap and easy to obtain, which is suitable for large-scale production. The catalytic synergy of the nickel-cobalt alloy, the excellent conductivity, large specific surface area and structural stability of the carbon nanofiber. At the same time, the NiCo alloy obtained by high-temperature calcination of NiCo-MOFs is loaded in the carbon nanofiber, and a bamboo-like morphology is successfully prepared. It is precisely because of its unique bamboo-like structure that an efficient catalytic network is formed inside the bamboo-like carbon nanofiber loaded with nickel-cobalt alloy. The bamboo-like nickel-cobalt alloy carbon nanofiber material prepared by the method not only enhances its structural stability, but also exposes abundant active sites, enhances its conductivity, reduces the overpotential in the catalytic process, and improves ion diffusion and electron transfer rate. The preparation method is simple, has excellent catalytic activity and durability, and thus obtains better OER performance.

[0008] One of the technical solutions of the present invention provides a method for preparing bamboo-shaped carbon nanofibers loaded with nickel-cobalt alloy, the steps are as follows:

[0009] a. Dissolve polyvinyl pyrrolidone (PVP), nickel nitrate hexahydrate, and cobalt nitrate hexahydrate in N,N-dimethylformamide (DMF) respectively, and stir evenly to obtain PVP solution, nickel nitrate solution, and cobalt nitrate solution respectively; add the prepared cobalt nitrate solution, nickel nitrate solution, and trimesic acid to the PVP solution at the same time, and stir evenly to obtain a mixed solution;

[0010] b. The mixed solution prepared in step a was transferred to an autoclave, placed in an oven, and heated to react;

[0011] c. After the reaction is completed, the reactor is taken out, and after it is cooled naturally, the solid reaction product is collected by centrifugation, washed and dried to obtain a purple spherical nickel-cobalt metal organic framework (NiCo-MOFs) powder;

[0012] d. Add polyacrylonitrile (PAN) to DMF, heat and stir to fully mix and dissolve it, then add nickel nitrate hexahydrate thereto, continue heating and stirring to completely dissolve it; then add NiCo-MOFs prepared in step c thereto, heat and stir to ensure that NiCo-MOFs are evenly dispersed in the solution;

[0013] e. placing the mixed solution obtained in step d on an electrospinning machine and electrospinning on aluminum foil to obtain a uniform purple fiber membrane;

[0014] f. The fiber membrane obtained in step e was peeled off from the aluminum foil and dried, and then placed in a muffle furnace for reaction to obtain a dark brown fiber membrane;

[0015] g. The dark brown fiber membrane obtained in step f is placed in a tubular furnace and heated for reaction to finally obtain black bamboo-like carbon nanofibers (NiCo@Ni-CNF) loaded with nickel-cobalt alloy.

[0016] Further, in step a, the concentration of the polyvinyl pyrrolidone (PVP) solution is 0.0167-0.0333 g / mL; the concentration of the nickel nitrate solution is 0.1-0.2 mM; the concentration of the cobalt nitrate solution is 0.1-0.133 mM; the dosage of the cobalt nitrate solution, the nickel nitrate solution, the trimesic acid and the PVP solution is 15 mL: 15 mL: 0.1-0.2 g: 30 mL; the stirring time is 30-40 min;

[0017] Furthermore, the autoclave in step b is preferably a stainless steel autoclave with a polytetrafluoroethylene liner; the heating reaction temperature is 130-160° C., and the time is 6-10 hours;

[0018] In some specific embodiments, the volume of the polytetrafluoroethylene-lined stainless steel autoclave in step b is 100 mL;

[0019] Furthermore, the washing and drying in step c is washing with anhydrous ethanol for 3 to 5 times to remove impurities; the washed solid product is placed in an oven for drying; the drying temperature is 60 to 80° C., and the drying time is 8 to 12 hours; in some specific embodiments, the oven in step c is a vacuum oven;

[0020] Furthermore, the amount of polyacrylonitrile (PAN), DMF, nickel nitrate hexahydrate, and NiCo-MOFs in step d is 0.5-1.5 g: 10 mL: 0.1-0.5 g: 0.1-0.5 g; the heating and stirring temperature is 60-90° C.; the heating and stirring time is 2-4 h for the first two times, and the stirring time for adding NiCo-MOFs is 20-24 h;

[0021] Furthermore, when performing electrospinning in step e, the mixed solution is first transferred into a syringe with a stainless steel needle and then placed on an electrospinning machine; the voltage of the electrospinning is 0.1 to 0.5 V, and the pushing speed of the syringe pump is 0.05 to 0.1 mm / min.

[0022] Furthermore, the drying in step f is preferably carried out in a vacuum oven; the drying temperature is 50-70° C. and the time is 8 hours; the reaction temperature in the muffle furnace is 200-300° C. and the time is 1-3 hours;

[0023] Furthermore, the heating reaction in step g is carried out in an inert gas environment, and the inert gas is preferably nitrogen; the temperature of the heating reaction is 700-900° C., and the time is 1-3 hours.

[0024] The second technical solution of the present application provides a nickel-cobalt alloy loaded bamboo-shaped carbon nanofiber prepared by the above technical solution.

[0025] The third technical solution of the present application provides the use of the above-mentioned bamboo-shaped carbon nanofiber loaded with nickel-cobalt alloy in oxygen evolution by electrolysis of water, wherein the bamboo-shaped carbon nanofiber loaded with nickel-cobalt alloy is used as a catalyst in oxygen evolution by electrolysis of water.

[0026] Compared with the prior art, the method of the present invention has the following obvious outstanding substantive features and significant advantages:

[0027] (1) The process of the present invention is simple and the reaction conditions are mild. A hydrothermal reaction is used to generate transition metal-based NiCo-MOFs, which are then mixed into a nickel-doped electrospinning solution for spinning to prepare bamboo-like carbon nanofibers (NiCo@Ni-CNF) loaded with nickel-cobalt alloy.

[0028] (2) The synthesis method is green and environmentally friendly, and the raw materials are cheap and easily available, which is suitable for large-scale production needs.

[0029] (3) The bamboo-shaped nickel-cobalt alloy carbon nanofiber material prepared by the present invention has good performance in hydrogen evolution by electrolysis of water, and exhibits low overpotential, high catalytic activity and durability. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1This is a scanning electron microscope (SEM) photograph of bamboo-shaped nickel-cobalt alloy carbon nanofibers prepared in an embodiment of the present invention;

[0031] Figure 2 This is the X-ray diffraction (XRD) pattern of the bamboo-shaped nickel-cobalt alloy carbon nanofibers prepared in an embodiment of the present invention;

[0032] Figure 3 The linear sweep voltammetry (LSV) curve of the bamboo-shaped nickel-cobalt alloy carbon nanofiber prepared in the embodiment of the present invention;

[0033] Figure 4 This is the current-time (it) curve of the constant potential test in the OER performance test of the bamboo-shaped nickel-cobalt alloy carbon nanofibers prepared in an embodiment of the present invention. DETAILED DESCRIPTION

[0034] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is described in detail below in conjunction with specific embodiments. It should be noted that the following embodiments will help those skilled in the art to further understand the present invention, but do not limit the present invention in any form. It should be noted that for those of ordinary skill in the art, several variations and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0035] All raw materials of the present invention are not particularly limited in their sources and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.

[0036] Example 1 A bamboo-like carbon nanofiber loaded with nickel-cobalt alloy

[0037] The process and steps of a method for preparing bamboo-shaped carbon nanofibers loaded with nickel-cobalt alloy provided in this embodiment are as follows:

[0038] a. First, 0.8g polyvinyl pyrrolidone (PVP) was dissolved in 30mL N,N-dimethylformamide (DMF) and stirred for 30min to obtain a polyvinyl pyrrolidone solution (PVP solution); 1.5mmol nickel nitrate hexahydrate and 1.5mmol cobalt nitrate hexahydrate were dissolved in 15mL DMF and stirred for 30min to obtain a nickel nitrate solution and a cobalt nitrate solution respectively. 15mL of the prepared cobalt nitrate solution, 15mL of the nickel nitrate solution, and 0.15g of trimesic acid were added to the PVP solution at the same time, stirred for 30min, and mixed evenly to obtain a mixed solution.

[0039] b. The mixed solution prepared in step a was transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave, placed in an oven, and heated at 150°C for 6 h.

[0040] c. After the reaction is completed, the reactor is removed and cooled naturally, and the solid reaction product is collected by centrifugation and washed three times with anhydrous ethanol to remove impurities. The washed solid product is placed in a vacuum oven at 60°C and dried overnight to obtain a nickel-cobalt metal organic framework (NiCo-MOFs) purple powder.

[0041] d. Add 1.0 g of polyacrylonitrile (PAN) to 10 mL of DMF and heat and stir at 80 ° C for 2 h to fully mix and dissolve it, then add 0.15 g of nickel nitrate hexahydrate, continue to heat and stir at 80 ° C for 2 h to completely dissolve it. Add 0.5 g of NiCo-MOFs obtained in step c to the above solution, heat and stir at 80 ° C for 20 h to ensure that NiCo-MOFs are evenly dispersed in the solution.

[0042] e. The mixed solution obtained in step d was transferred into a syringe with a stainless steel needle, placed on an electrospinning machine, and electrospinned on aluminum foil to obtain a uniform purple fiber membrane; the electrospinning voltage was 0.22 kV, and the pushing speed of the syringe pump was 0.09 mm / min.

[0043] f. The fiber membrane obtained in step e was peeled off from the aluminum foil, dried in a vacuum oven at 60° C. for 8 h, and then placed in a muffle furnace and reacted at 260° C. for 2 h to obtain a dark brown fiber membrane.

[0044] g. The dark brown fiber membrane obtained in step f was placed in a tubular furnace and heated to react for 2 h at 800 ° C under nitrogen conditions to finally obtain black bamboo-like carbon nanofibers loaded with nickel-cobalt alloy.

[0045] Example 2 Test of electrocatalytic oxygen evolution reaction (OER) of bamboo-shaped carbon nanofibers loaded with nickel-cobalt alloy

[0046] In order to verify the OER performance of the bamboo-shaped carbon nanofiber loaded with nickel-cobalt alloy of the present invention, the OER performance of the electrode material was systematically studied in a three-electrode system with 1M KOH as the electrolyte using an electrochemical workstation (Metrohm Autolab, M204). Hydrogen production performance test by electrolysis of water: 6 mg of nickel-cobalt alloy carbon nanofiber catalyst, 10 μL of Nafion, and 300 μL of water and alcohol were placed in a 1 mL reagent bottle, ultrasonicated for 1 h, and then dripped onto nickel foam (NF) and ensured that the drop coating area was 1*1 cm 2 After drying, the prepared foam was sandwiched on the working electrode and the electrochemical performance was tested in a three-electrode system, and the electrolyte was 1M potassium hydroxide. The counter electrode used in this embodiment was a stone mill rod electrode, and the reference electrode was a mercury / mercuric oxide electrode, model R501-A, both purchased from Shanghai Yueci Electronics Co., Ltd. Specifically comprising the following steps:

[0047] Before the electrochemical test, all electrodes were immersed in 1 M KOH electrolyte for more than 8 h and charged at 100 mV s in the potential range of 0 to 0.8 V (vs. Hg / HgO). -1 The CV scan was performed for 50 cycles at a scan rate of 1000 nm to ensure that the surface active material had reached an electrochemically stable state in the subsequent test. -2 The corresponding current is used for chronopotentiometry. All potentials in this patent are based on formula E RHE =E Hg / HgO +0.059×pH+0.098 was converted into reversible hydrogen electrode potential (RHE).

[0048] Figure 1 This is a scanning electron microscope (SEM) photograph of the bamboo-shaped nickel-cobalt alloy carbon nanofibers prepared in an embodiment of the present invention. It can be seen that the material forms a bamboo-shaped morphology, and the NiCo-MOfs derivatives are evenly distributed therein.

[0049] Figure 2 This is the X-ray diffraction (XRD) pattern of the bamboo-shaped nickel-cobalt alloy carbon nanofibers prepared in the embodiment of the present invention. By comparing it with the NiCo alloy standard PDF card (PDF#04-004-8490), it can be seen that the NiCo-MOFs derivative was successfully synthesized and successfully loaded in the nickel-doped carbon nanofibers.

[0050] Figure 3 The linear sweep voltammetry (LSV) curve of the bamboo-shaped nickel-cobalt alloy carbon nanofibers prepared in this example is shown in Figure 1. The experiment was conducted at a potential range of 0.8-0 V (vs. Hg / HgO) at a rate of 5 mV s -1 The negative scan was performed at a scan rate of 1000 Hz. It can be seen that the initial overpotential of the material is small, close to 0 mV. -2 At a current density of 2.5 Å, the overpotential is only 248 V, which has a low overpotential and exhibits excellent OER performance, surpassing most OER electrocatalysts.

[0051] Figure 4 This is the OER constant potential test current-time (it) curve of bamboo-shaped nickel-cobalt alloy carbon nanofibers. After 200 hours of continuous catalysis, the initial current retention rate is still nearly 90%, which has excellent cycle stability.

[0052] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A method for preparing bamboo-shaped carbon nanofibers loaded with nickel-cobalt alloy, characterized in that: The preparation method is as follows: a. Dissolve polyvinyl pyrrolidone, nickel nitrate hexahydrate, and cobalt nitrate hexahydrate in N,N-dimethylformamide, respectively, and stir to obtain polyvinyl pyrrolidone solution, nickel nitrate solution, and cobalt nitrate solution, respectively; add the prepared cobalt nitrate solution, nickel nitrate solution, and trimesic acid to the polyvinyl pyrrolidone solution at the same time, and stir to obtain a mixed solution; b. The mixed solution prepared in step a was transferred to an autoclave, placed in an oven, and heated to react; c. After the reaction is completed, the reactor is taken out, and after it is cooled naturally, the solid reaction product is collected by centrifugation, washed and dried to obtain a purple spherical nickel-cobalt metal organic framework NiCo-MOFs powder; d. Add polyacrylonitrile to N,N-dimethylformamide, heat and stir to fully mix and dissolve, then add nickel nitrate hexahydrate, continue heating and stirring to completely dissolve; then add NiCo-MOFs prepared in step c, heat and stir to ensure that NiCo-MOFs are evenly dispersed in the solution; e. placing the mixed solution obtained in step d on an electrospinning machine and electrospinning on aluminum foil to obtain a uniform purple fiber membrane; f. The fiber membrane obtained in step e was peeled off from the aluminum foil and dried, and then placed in a muffle furnace for reaction to obtain a dark brown fiber membrane; g. placing the dark brown fiber membrane obtained in step f in a tubular furnace, heating and reacting, and finally obtaining black bamboo-like carbon nanofibers loaded with nickel-cobalt alloy.

2. The method for preparing bamboo-shaped carbon nanofibers loaded with nickel-cobalt alloy according to claim 1, characterized in that: In step a, the concentration of the polyvinyl pyrrolidone solution is 0.0167-0.0333 mM; the concentration of the nickel nitrate solution is 0.1-0.2 mM; the concentration of the cobalt nitrate solution is 0.1-0.133 mM; the dosage relationship of the cobalt nitrate solution, the nickel nitrate solution, the trimesic acid and the polyvinyl pyrrolidone solution is 15 mL: 15 mL: 0.1-0.2 g: 30 mL; and the stirring time is 30-40 min.

3. The method for preparing bamboo-shaped carbon nanofibers loaded with nickel-cobalt alloy according to claim 1, characterized in that: The temperature of the heating reaction in step b is 130-160° C. and the time is 6-10 hours.

4. The method for preparing bamboo-shaped carbon nanofibers loaded with nickel-cobalt alloy according to claim 1, characterized in that: The drying temperature in step c is 60-80° C. and the drying time is 8-12 hours.

5. The method for preparing bamboo-shaped carbon nanofibers loaded with nickel-cobalt alloy according to claim 1, characterized in that: The dosage of polyacrylonitrile, N,N-dimethylformamide, nickel nitrate hexahydrate, and NiCo-MOFs in step d is 0.5-1.5 g: 10 mL: 0.1-0.5 g: 0.1-0.5 g; the heating and stirring temperatures are all 60-90° C.; the heating and stirring times are both 2-4 h for the first two times, and the stirring time for adding NiCo-MOFs is 20-24 h.

6. The method for preparing bamboo-shaped carbon nanofibers loaded with nickel-cobalt alloy according to claim 1, characterized in that: The voltage of the electrospinning in step e is 0.1-0.5 V, and the pushing speed of the syringe pump is 0.05-0.1 mm / min.

7. The method for preparing bamboo-shaped carbon nanofibers loaded with nickel-cobalt alloy according to claim 1, characterized in that: The drying temperature in step f is 50-70° C. and the time is 8 hours; the reaction temperature in the muffle furnace is 200-300° C. and the time is 1-3 hours.

8. The method for preparing bamboo-shaped carbon nanofibers loaded with nickel-cobalt alloy according to claim 1, characterized in that: The heating reaction in step g is carried out in an inert gas environment; the temperature of the heating reaction is 700-900° C. and the time is 1-3 hours.

9. A bamboo-like carbon nanofiber loaded with nickel-cobalt alloy, characterized in that: The carbon nanofiber is obtained by the method for preparing bamboo-shaped carbon nanofiber loaded with nickel-cobalt alloy described in any one of items 1 to 8.

10. An application of bamboo-like carbon nanofibers loaded with nickel-cobalt alloy in oxygen evolution by electrolysis of water, characterized in that: The bamboo-shaped carbon nanofiber loaded with nickel-cobalt alloy is used as a catalyst in the electrolysis of water for oxygen evolution.

Citation Information

Patent Citations

  • Bamboo-like nitrogen-doped carbon nanofiber coated transition metal alloy nanoparticle catalytic material for efficient bifunctional electrocatalysis

    CN111068734A

  • Nickel-cobalt-nitrogen co-doped carbon / carbon fiber composite electrocatalyst with parallel array structure as well as preparation method and application of nickel-cobalt-nitrogen co-doped carbon / carbon fiber composite electrocatalyst

    CN116555821A

  • Preparation method of nitrogen-doped carbon fiber loaded Ni-MoC nanoparticles for electro-catalytic hydrogen evolution in full pH range

    CN119061427A